Effects of frying on fish, fish products and frying oil - a review - S., NurSyahirah; A., Rozzamri (Rynnye Lyan Resources, 2022)
Fish and fish products contain important source of nutrient that provides benefits upon consumption. The increasing demand and high utilization of fish have caused a market shift in the fishery industry. Although fish is nutritious, some consumers do not prefer to consume fish in its original form because of its fishy taste, fishy odour and it is highly perishable. To further promote the consumption of fish, the production of fish products and frying are applied to suit consumers’ preferences. Frying is commonly used in various food premises as it changes the characteristics of the fish and fish products, especially the taste and texture. However, the increase in awareness has changed the perception of the consumer as they prefer healthier food in their lifestyle. Despite the increase in awareness, some consumers still prefer fried foods and food products due to their unique sensory properties and texture. To understand the effects of frying on foods, several parameters during frying are studied. Frying temperature, frying cycle, frying time, frying techniques and frying oils used are parameters that could affect the physicochemical and sensory attributes of the fish and fish products. Repetitive frying could cause the formation of toxins and alter the fatty acid content in the fish, fish products and frying oils. This changes the taste and alters the composition of the foods. Meanwhile, different frying times, oil and techniques cause significant changes to the chemical composition, sensory attributes, lipid oxidation, fat content, oil absorption and fatty acid profiles of the fish and fish product. This review aimed to gather information specifically on the changes in fish and fish products upon frying at different frying cycles, time, temperature, oils, and techniques.